Internal carbonation of belite-rich Portland cement: An in-depth observation at the interaction of the belite phase with sodium bicarbonate. (December 2021) - Seo, Joonho; Kim, Seonhyeok; Jang, Daeik; Kim, Hayeon; Lee, H.K.
Abstract: The potential for the internal carbonation of belite-rich Portland cement with the addition of sodium bicarbonate is proposed in the present study with a particular observation of the microstructural evolution of the belite phase. Cement paste samples having additional dosages of NaHCO3 of 0, 1, 2, and 5 wt% were fabricated and characterized by means of X-ray diffractometry, pH measurements, thermogravimetry analyses, isothermal calorimetry, and solid-state 29 Si nuclear magnetic resonance spectroscopy. The test results indicated that the CO2 released from the added NaHCO3 was uniformly dissolved in the matrix, facilitating internal carbonation. In addition, the formation of C–S–H was further promoted upon the incorporation of NaHCO3, signifying a reaction of belite with the NaHCO3 . Isothermal calorimetry results confirmed that the NaHCO3 enhanced the early reaction kinetics. Meanwhile, the pH value of the samples increased due to the anion exchange between the NaHCO3 and Ca(OH)2 . Highlights: NaHCO3 was added to belite-rich Portland cement paste. NaHCO3 incorporation promoted the reaction of belite by the internal carbonation. NaHCO3 incorporation enhanced the early reaction kinetics. Despite the consumption of portlandite, NaHCO3 maintained or even increased pH level.